2016
DOI: 10.1007/s11356-016-6110-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking fluorescent dissolved organic matter in multistage rivers using EEM-PARAFAC analysis: implications of the secondary tributary remediation for watershed management

Abstract: Profound understanding of behaviors of organic matter from sources to multistage rivers assists watershed management for improving water quality of river networks in rural areas. Ninety-one water samples were collected from the three orders of receiving rivers in a typical combined polluted subcatchment (diffuse agricultural pollutants and domestic sewage) located in China. Then, the fluorescent dissolved organic matter (FDOM) information for these samples was determined by the excitation-emission matrix coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Interestingly, despite the fact that riparian soils had a higher degree of humi cation than sediments, the uorescence index revealed that humus in both sediments and riparian soils was mostly produced from biogenic sources (Nebbioso &Piccolo 2013). Compared with C1, C2 has an obvious red shift in emission wavelength, indicating that C2 has higher aromatization and molecular weight, and its molecular structure is relatively stable (Nie et al 2016). The C3 component (Ex/Em = 270,360 nm/460 nm) has only one excitation peak and one emission peak, which is de ned as the tryptophan-like uorescent component and is also believed to be increased by polypeptide substances produced by microbial activities, such as human sewage or algae eutrophication.…”
Section: Abundance and Properties Of Dommentioning
confidence: 99%
“…Interestingly, despite the fact that riparian soils had a higher degree of humi cation than sediments, the uorescence index revealed that humus in both sediments and riparian soils was mostly produced from biogenic sources (Nebbioso &Piccolo 2013). Compared with C1, C2 has an obvious red shift in emission wavelength, indicating that C2 has higher aromatization and molecular weight, and its molecular structure is relatively stable (Nie et al 2016). The C3 component (Ex/Em = 270,360 nm/460 nm) has only one excitation peak and one emission peak, which is de ned as the tryptophan-like uorescent component and is also believed to be increased by polypeptide substances produced by microbial activities, such as human sewage or algae eutrophication.…”
Section: Abundance and Properties Of Dommentioning
confidence: 99%
“…These contaminants originate from both point and non-point sources. Stormwater runoff is another major contamination transport route, which brings treated and untreated sewage, industrial waste, petroleum hydro-chemicals and road dust into the river water [6].…”
Section: Sources Of River Water Pollutionmentioning
confidence: 99%
“…The construction of hydraulic structures such as irrigation weirs or irrigation infrastructure reduces water flow velocity but increases hydraulic retention time, which facilitate sedimentation, aeration, sunlight irradiation and anaerobic reactions, resulting in improving water quality of river [6,8].…”
Section: Building Hydraulic Structuresmentioning
confidence: 99%
See 2 more Smart Citations